STRATEGI PEMBELAJARAN AGAMA HINDU ABAD 21 - Putu Eka Sastrika Ayu (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The primary role of teachers and schools is to equip students with new literacy, competence for the productive use of information technology, and a fairly disciplined conceptual knowledge base. This requires a change of student-centered learning. In such contexts, the teacher is a learning designer, the teacher's ability to plan learning in accordance with 21st century characteristics, one of them using a learning strategy. The material in the religious subjects is abstract, so it is necessary that the strategy can make students feel the benefits of learning in a konkrite.